Exploring relationships between conservation and poverty reduction in wetland ecosystems: lessons from 10 integrated wetland conservation and poverty reduction initiatives - Senaratna Sellamuttu, Sonali; de Silva, Sanjiv; Nguyen-Khoa, Sophie (Informa UK Limited, 2011)
It is well known that whilst wetlands deliver a wide range of services vital for human well-being, they are being rapidly degraded and lost. Losses tend to be higher where human populations are increasing most and demands for economic development are greatest. Multidisciplinary management approaches that integrate conservation and development objectives in wetlands are therefore urgently requested for by the Ramsar Convention on Wetlands. This paper describes the evaluation of 10 wetland management case studies from Asia, Africa and South America that adopted such an integrated approach. The evaluation assessed the outcomes of these integrated initiatives to identify conditions and processes for linking conservation and poverty reduction objectives in wetlands. The findings are also compared with other assessments of integrated approaches, particularly in terms of their effectiveness in optimizing conservation and poverty reduction outcomes. The results from our studies suggest an ongoing evolution of such integrated interventions, which also implies cycles of learning from past mistakes. Overall, our results highlight the significant variation between wetlands in types and quantities of services they provide and emphasize the need to view many ecological issues as social challenges for equitable solutions to both wetlands and people. The analysis further shows that the positive on-ground results owe much to the interdisciplinary problem analysis, whereby interventions can move from treating symptoms to addressing root causes. While no blueprint emerged on how to successfully integrate conservation and poverty reduction in wetlands, important lessons for future interventions were drawn.